2002
DOI: 10.1590/s0034-89102002000600006
|View full text |Cite
|
Sign up to set email alerts
|

Perfil dos acidentes de trabalho em refinaria de petróleo

Abstract: The study results showed that there is a predominance of accidents in lower hierarchy workers, and these accidents occur mainly during maintenance activities. There is a need to improve the company's accident reporting system and accident investigation procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 5 publications
0
6
0
12
Order By: Relevance
“…These measures are feasible through the correlation of scientific data and national health databases and should anticipate possible health outcomes with repercussions on public health and the environment. The results of the present diagnosis indicate a lack of concern for vulnerable groups and for chemical exposure and other occupational liabilities common in refineries (Souza and Freitas, 2002).…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…These measures are feasible through the correlation of scientific data and national health databases and should anticipate possible health outcomes with repercussions on public health and the environment. The results of the present diagnosis indicate a lack of concern for vulnerable groups and for chemical exposure and other occupational liabilities common in refineries (Souza and Freitas, 2002).…”
Section: Discussionmentioning
confidence: 68%
“…We observed that environmental impact studies overestimate the estimated positive impacts such as generating jobs and taxes, while ignoring the potential of accidents and occupational diseases (Augusto, 1991(Augusto, , 1995Souza Freitas, 2002).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations